Unilateral chorioretinitis in early latent syphilis - Sanjeev Kumar Dhoot (Oman Journal of Ophthalmology, 2025)
An interesting and unusual case of a 42-year-old Indian male with unilateral chorioretinitis, optic disc inflammation, and positive syphilis serology is presented, highlighting the need for a high index of suspicion in diagnosing this “great masquerader” with diverse manifestations.